MAKING PHYSICS LEARNING MEDIA BASED ON HOTS FOR SMP LEVELS - Saut Dohot Siregar; Nurul Khairina; Robin Robin (Universitas Negeri Medan, 2020)
Learning outcomes can be influenced by learning models, learning styles, and learning media. The accuracy of the learning media used can increase students' thinking power even to higher levels of thinking. High-level thinking students can be trained through learning in class. Learning media that is suitable for teaching material can help students in thinking at a high level or HOTS so learning media are needed in the teaching and learning process. This study aims to create learning media and try out these media. Learning media developed using the Borland Delphi application. The learning media developed were tested in junior high school grade 8 in Medan. The research sample was taken by cluster random sampling where each school had the same opportunity to become a research sample. Samples were divided into categories group A and group B. Group A and group B were subjected to the normality and homogeneity tests. This study uses research instruments in the form of multiple-choice questions as many as 15 questions and questionnaires on students' opinions on the learning media used. The results showed that the learning process by using instructional media produces better or higher learning outcomes than the learning process without the use of instructional media. The average posttest students in the class using media developed higher than the average posttest students in the class who do not use instructional media. The results of the student questionnaire argue that the media need to be designed to be more interesting so that students are happier to use it